Analisis Kerawanan Pada Aplikasi Website Menggunakan Standar OWASP Top 10 Untuk Penilaian Risk Rating - Hermawan Setiawan; Lytio Enggar Erlangga; Syubbanul Siddiq; Yusuf Atha Gunawan (Info Kripto, 2023)
Since 2011, SMA N “ABC” has implemented a web-based information system. The information system is intended as an introduction to information and learning media for students. The system has never been audited and/or tested for security, so the vulnerability is not yet known. To test the security of the SI SMA N “ABC” application, vulnerability scanning and vulnerability assessment were carried out using the Open Web Application Security Project (OWASP) Top 10 Security Risk 2017 and the Open Web Application Security Project (OWASP) Risk Rating Methodology. From the results of scanning vulnerabilities found thirteen vulnerabilities ranging from high to low categories. Based on the assessment of detected vulnerabilities, resulting in a scale of 5.72 for the possibility of vulnerabilities being exploited by attackers and a scale of 3,315 for the impact on business processes at SMA N “ABC”